Effects of Different Shading Treatments on the Biomass and Transcriptome Profiles of Tea Leaves (Camellia sinensis L.) and the Regulatory Effect on Phytohormone Biosynthesis - Fang, Zhou-Tao; Jin, Jing; Ye, Ying; He, Wei-Zhong; Shu, Zai-Fa; Shao, Jing-Na; Fu, Zhu-Sheng; Lu, Jian-Liang; Ye, Jian-Hui (Frontiers in Plant Science, 2022)
Our previous study showed colored net shading treatments had comparable effects on the reduction of bitter and astringent compounds flavonol glycosides in tea leaves, compared with black net shading treatment, whereas the effects on the biomass and phytohormones are still unclear. Here, we investigated the phytohormone and transcriptome profiles of tea leaves under different shading treatments, using black, blue and red nets with the same shade percentages. The bud density, fresh weight of 100 buds and yield under blue net shading treatments were greatly elevated by 2.00 folds, 1.24 folds and 2.48 folds, compared with black net shading treatment, while their effects on flavonoid composition were comparable to black net shading treatment. The transcriptome profiles of different shade net-treated samples were well resolved and discriminated from control. The KEGG result indicated that the pathways of phenylpropanoid biosynthesis, MAPK signaling pathways and plant hormone signal transduction were differentially regulated by different shading treatments. The co-expression analysis showed the contents of salicylic acid and melatonin were closely correlated with certain light signal perception and signaling genes (p < 0.05), and UVR8, PHYE, CRY1, PHYB, PHOT2, and HY5 had more close interactions with phytohormone biosynthetic genes (p < 0.05). Our results suggest that different shading treatments can mediate the growth of tea plants, which could be attributed to the regulatory effect on phytohormones levels, providing an instruction for the production of summer/autumn tea and matcha.